FIGURE 1. Ceramaster patagonicus australis. USNM 1121579. A. Abactinal surface. B in Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zenodo, 2011)
FIGURE 1. Ceramaster patagonicus australis. USNM 1121579. A. Abactinal surface. B. Close-up of abactinal plates. C. Close-up of armtip showing superomarginal plate series. D. Actinal surface. E. Close-up of actinal surface showing mouth and furrow spination. Scale Bar = 0.5 cm. Published as part of Mah, Christopher L., 2011, Taxonomy of high-latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa, pp. 1-48 in Zootaxa 2759 on page 7, DOI: 10.5281/zenodo.276783